The Routledge handbook of autocratization - Croissant, Aurel; Tomini, Luca (Routledge, Taylor & Francis Group, 2024)
"The Routledge Handbook of Autocratization comprehensively and systematically explores the current understanding, and unchartered research paths, of autocratization. With wide-reaching regional coverage and expert analysis from Asia, North and South America, Europa, the Middle East and North Africa, this handbook reveals cross-country, and cross-regional, analysis and insights and presents in-depth explanations and consequences of autocratization. Arranged in five thematic sections, chapters explore the basic aspects of conceptualization, theorization, and measurement of autocratization; the role of various political and non-political actors as perpetrators, supporters, bystanders, or defenders of democracy against autocratization processes; and the consequences across various policy fields. Showcasing cutting-edge research developments, the handbook illustrates the deeply complex nature of the field, examining important topics in need of renewed consideration at a time of growing concerns for democracy and the global spread of authoritarian challenges to democracy. The Routledge Handbook of Autocratization will be a key reference for those interested in, and studying authoritarianism, democratization, human rights, governance, democracy and more broadly comparative politics, and regional/area studies"--
Literaturverzeichnisse, Literaturhinweise, Index
Rückseite Titelblatt: "Chapter 2 of this book is freely available as a downloadable Open Access PDF ..."
Keywords: Erde; Aufsatzsammlung